Co-Catalyzed decarbonylative alkylative esterification of styrenes with aliphatic aldehydes and hypervalent iodine(iii) reagents. Issue 17 (16th July 2019) - Peng, Yong; Jiang, Yuan-Yuan; Du, Xue-Jiao; Ma, Da-You; Yang, Luo
Abstract : Decarbonylation of aliphatic aldehydes into 1°, 2° and 3° alkyl radicals to construct C(sp 3 )–C(sp 3 ) bond via radical addition and C(sp 3 )–O bond via the interconversion of Co II –Co III –Co I . Abstract : A convenient Co-catalyzed three-component decarbonylative alkylative esterification of styrene derivatives with aliphatic aldehydes and iodobenzene diacetate to provide chain elongated acetates and benzoates has been developed. Readily available aliphatic aldehydes are decarbonylated into 1°, 2° and 3° alkyl radicals for the construction of a C(sp 3 )–C(sp 3 ) bond via radical addition and an interconversion of Co II –Co III –Co I complexes is accountable for the formation of a C(sp 3 )–O bond.